The Influence of Psychological Factors on Ethical Decision Making in Islamic Educational Institutions at Sma Plus Assalaam - Ahsyaf Muzakki; Mulyawan Safwandy Nugraha (al-Afkar, Journal For Islamic Studies, 2025)
This article aims to examine the influence of psychological factors on ethical decision-making in Islamic educational institutions. The research method used in this article is qualitative with a descriptive approach. Data collection techniques include: first, in-depth interviews; second, participant observation; and third, documentation. The data collected through these three techniques were then validated through credibility checks. The research findings on the influence of psychological factors on ethical decision-making at SMA Plus Assalaam. The module project "The Influence of Psychological Factors on Ethical Decision-Making" provides an important contribution to understanding issues within institutions. By raising awareness of psychological factors and biases, building emotion management skills, and encouraging collaboration, this module helps educational institutions make more ethical, rational, and sustainable decisions. It also plays a role in creating a healthier organizational culture and improving the well-being of all members of the institution.